2016
DOI: 10.5688/ajpe80110
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Analysis of Written Reflections during a Teaching Certificate Program

Abstract: Objective. To evaluate the success of a teaching certificate program by qualitatively evaluating the content and extent of participants' reflections. Methods. Two investigators independently identified themes within midpoint and final reflection essays across six program years. Each essay was evaluated to determine the extent of reflection in prompted teaching-related topic areas (strengths, weaknesses, assessment, feedback). Results. Twenty-eight themes were identified within 132 essays. Common themes encompa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Incorporating reflective discussions into a course may be one way to help students develop skills related to Bloom's affective domain. Although use of reflective activities is described in the pharmacy literature, [28][29][30][31][32] there are no studies examining the use of these activities in the context of psychiatric and substance use disorders. The process of reflection helps learners connect personal experiences with those of others and permits the integration of new knowledge into existing understanding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Incorporating reflective discussions into a course may be one way to help students develop skills related to Bloom's affective domain. Although use of reflective activities is described in the pharmacy literature, [28][29][30][31][32] there are no studies examining the use of these activities in the context of psychiatric and substance use disorders. The process of reflection helps learners connect personal experiences with those of others and permits the integration of new knowledge into existing understanding.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the health professions literature reported that use of reflection was valuable in building self-awareness, developing professional attitudes, and building criticalthinking skills and cultural competence. 28,31,33,34 Incorporating reflective discussion created an opportunity whereby learners shared ideas and encountered others' viewpoints. Frequently these exchanges provided the learner with opportunities for further reflection and refinement of their original perspectives.…”
Section: Discussionmentioning
confidence: 99%
“…Successful professionals must be able to reflect on their experience in order to find solutions to complex problems encountered on a daily basis. Such reflection is necessary in order for nursing students to improve their performance, and must be applied by nursing students committed to professional growth as lifelong learners (Castleberry et al, 2016). In reflections, nursing students wrote narratives, as human experience is always narrated and focuses on observations (Žydžiūnaitė, 2015).…”
Section: Data Collectionmentioning
confidence: 99%
“…A qualitative approach was selected for this study because this method allows for deep and rich analysis of text and image not so easily obtainable from survey-based research [25]. The essence of qualitative content analysis is identifying substantive statements that really reveal something to the researcher.…”
Section: Methodlogymentioning
confidence: 99%